Predictors of three-month mortality among patients with kidney failure without access to dialysis in Tanzania - Azim, Ali; Nkwera, Upendo; Msangi, Elizabeth; Shoo, Jacqueline; Mngumi, Jonathan; Shoo, May; Batanyita, Julieth; Kweka, Garvin; Jonathan, Irene; Paulo, David; Mlay, Jackson; Punatar, Priyank; et al. (African Journal of Nephrology, 2026)
Background: Chronic kidney disease (CKD) is a growing public health concern in Africa, including East Africa, where access to kidney replacement therapy (KRT) remains limited due to economic and infrastructural barriers. As a result, many patients with kidney failure receive unstructured non-dialysis medical care rather than formal conservative kidney management (CKM) programmes. This study aimed to evaluate short-term outcomes and identify predictors of three-month mortality among kidney failure patients on non-dialysis medical management at Muhimbili National Hospital (MNH), Tanzania. Methods: We conducted a 90-day prospective cohort study of adults (≥18 years) with CKD stage 5 who were eligible for haemodialysis but unable to afford it between October and December 2024. Survival was analysed using Kaplan–Meier methods, and mortality predictors were assessed using Cox regression. Ethical approval was obtained from the MUHAS Research and Publications Committee (Ref: MUHAS-REC-08-2024-2415). Results: A total of 172 kidney failure patients were enrolled, with a median age of 60 years and 90-day mortality rate was 24.3%. In multivariate analysis, predictors of mortality included no monthly income (aHR: 3.68, P = 0.031), difficulty in breathing at baseline (aHR: 2.59, P = 0.020), cancer history (aHR: 4.71, P = 0.002), and hyperkalaemia (aHR: 2.34, P = 0.030). Our study highlighted that lack of income, difficulty in breathing, malignancy, and hyperkalaemia predicted shortterm mortality in kidney failure patients who could not access dialysis, reflecting both clinical and socioeconomic vulnerability. Conclusion: There is an urgent need for context-specific CKM guidance and policy interventions to support this underserved population in resource-limited settings.